Analisis Puisi “Senja Di Pelabuhan Kecil” Melalui Pendekatan Struktural (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Literary works are arts that have elements of mind, imagination, and emotion. In addition, it is also referred to as creative work that is used as intellectual and emotional consumption. Poetry is a type of literature with language bound by rhythm, rhyme, and the arrangement of stanzas and arrays. Poetry is able to express the emotions and experiences of memorable writers and then poured into a rhyming language style so that it is more interesting to read. The author is interested in analyzing the poem